2018
DOI: 10.1016/j.stem.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

FOXD3 Regulates Pluripotent Stem Cell Potential by Simultaneously Initiating and Repressing Enhancer Activity

Abstract: SUMMARYEarly development is governed by the ability of pluripotent cells to retain the full range of developmental potential and respond accurately to developmental cues. This property is achieved in large part by the temporal and contextual regulation of gene expression by enhancers. Here, we evaluated regulation of enhancer activity during differentiation of embryonic stem to epiblast cells and uncovered the forkhead transcription factor FOXD3 as a major regulator of the developmental potential of both pluri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 40 publications
6
34
1
Order By: Relevance
“…Epigenetic factors could regulate diverse developmental and disease processes. A previous study had shown that FOXD3 could target the super‐enhancer in mouse embryonic stem cells, thus regulating the exit from naive pluripotency and transition to a primed pluripotent state . Here, we found FOXD3 functioned as the repressor of WDR5 in TIC, providing a novel mechanism underlying the regulatory effect of FOXD3 on tumor initiation and metastasis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Epigenetic factors could regulate diverse developmental and disease processes. A previous study had shown that FOXD3 could target the super‐enhancer in mouse embryonic stem cells, thus regulating the exit from naive pluripotency and transition to a primed pluripotent state . Here, we found FOXD3 functioned as the repressor of WDR5 in TIC, providing a novel mechanism underlying the regulatory effect of FOXD3 on tumor initiation and metastasis.…”
Section: Discussionmentioning
confidence: 58%
“…FOXD3 is also an early molecular marker of neural crest cells and was responsible for the repression of melanogenesis in early migratory neural crest cells . The role of FOXD3 in stem cells is further demonstrated by facilitating the exit from naive pluripotency and transition to a primed pluripotent state . Recent studies have suggested parallels between embryonic stem cells and TICs, which is highlighted by the shared transcription factors involved .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of developmental genes change their A/B compartment status during embryo development. For example, Foxd3, a pluripotency factor (Krishnakumar et al, 2016), is located in the B compartment in sperm, but changed to the A compartment in embryos ( Figure S5D).…”
Section: The Association Between Chromatin Structures and Embryonic Dmentioning
confidence: 99%
“…However, it is not clear what directs BAF complexes to these promoters. In addition, it has also been shown that forkhead box D3 (FOXD3), a TF that binds before Oct4, can recruit BRG1 to chromatin, demonstrating an involvement of FOXD3 in the interactions between chromatin remodeling and ES cell reprogramming factors . This suggests that non‐reprogramming factors in ES cells can induce chromatin remodeling.…”
Section: Chromatin Remodeling Factors Aid In the Recruitment Of Pionementioning
confidence: 99%